Silicon waveguide multiplexed sensor array configuration for label-free biosensing applications - Prabhathan, Patinharekandy (2015)
This article reviews different waveguide based architectures forlabel-free detection of biomolecules. Working principles of various configurationsare discussed with an emphasis on their sensing principle and sensitivity. Later part of the article demonstrates a silicon waveguide Bragg grating resonator array as a highly sensitive refractive index sensor device for multiplexed detection of multi-analytes. Main features of the sensor element are discussed through numerical simulation, and proof-of concept device is demonstrated through micro fabrication. The proposed configuration of silicon waveguide based sensor array is expected to find potential application in portable chip based devices as highly sensitive multiplexed biosensors.